Characteristics of Myopia Patient at Roemani Muhammadiyah Hospital Semarang - Lingga Dwi; Swasty; Wahju Ratna Martiningsih; Andra Novitasari (Universitas Muhammadiyah Malang, 2025)
Background : Myopia is the most common cause of visual impairment in the world with a prevalence of more than 28% and continues to increase, it is even predicted that by 2050 myopia will affect half of the world’s population or 5 billion people. The aim of the study was to describe the characteristics of myopia patients at the Roemani Muhammadiyah Hospital Semarang. Methods : Quantitative analytical observational research with a cross sectional design, used primary and secondary data from January-September 2023 at the Roemani Muhammadiyah Hospital Semarang. Data were analyzed descriptively. Result : The total research sample of 77 respondents showed the results of myopia patient aged < 20 years when the growth of the axial length of the eyeball had not stopped (51.9%), female gender (66.2%), no parental history of myopia (57.1%), patient lived in urban areas (94.8%), and had a high school education (51.9%). Conclusion : Most of the patients diagnosed with myopia < 20 years old and female. Patients predominantly have no history of myopia in their parents and live in urban areas, and the education level of most patients is high school.